2013
DOI: 10.1093/jxb/ert027
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and physiological changes in the S assimilation pathway due to single or combined S and Fe deprivation in durum wheat (Triticum durum L.) seedlings

Abstract: The effect of iron (Fe) and sulphur (S) deprivation on sulphate uptake and assimilation pathways was investigated in durum wheat by analysing the expression of genes coding for major transporters and enzymes involved in sulphate assimilation and reduction: high-affinity sulphate transporters (TdSultr1.1 and TdSultr1.3), ATP sulphurylase (TdATPSul1 and TdATPSul2), APS reductase (TdAPR), sulphite reductase (TdSiR), O-acetylserine(thiol)lyase (TdOASTL1 and TdOASTL2), and serine acetyltransferase (TdSAT1 and TdSAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 50 publications
4
57
4
Order By: Relevance
“…It is of interest to place our findings in the context of studies that have reported on the general effects of Fe deficiency on chlorophyll synthesis and photosynthesis that have been well documented in the literature (Spiller and Terry, 1980;Andaluz et al, 2006;Nishio and Terry, 1983;Nishio et al, 1985;Sharma, 2007;Timperio et al, 2007;Laganowski et al, 2009;Msilini et al, 2011;Ciaffi et al, 2013;Paolacci et al, 2014;Rodríguez-Celma et al, 2013). Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinssupporting
confidence: 61%
“…It is of interest to place our findings in the context of studies that have reported on the general effects of Fe deficiency on chlorophyll synthesis and photosynthesis that have been well documented in the literature (Spiller and Terry, 1980;Andaluz et al, 2006;Nishio and Terry, 1983;Nishio et al, 1985;Sharma, 2007;Timperio et al, 2007;Laganowski et al, 2009;Msilini et al, 2011;Ciaffi et al, 2013;Paolacci et al, 2014;Rodríguez-Celma et al, 2013). Some studies on Fe depletion in plants reported that PSI was the major target of Fe deficiency (Nishio et al, 1985;Timperio et al, 2007), whereas we saw a major effect on the cytochromeb 6 f complex and less on PSI.…”
Section: Fe Sparing In Chloroplasts Targets Abundant Fe Proteinssupporting
confidence: 61%
“…Moreover, S-depleted Chlamydomonas cells have been used for microarrayand RNA-seq-based transcript abundance studies (Zhang et al, 2004;Nguyen et al, 2008;González-Ballester et al, 2010), determination of metabolite profiles (Bölling and Fiehn, 2005), and the production of H 2 (Ghirardi et al, 2007). Numerous studies of S-deprived plants have also been performed (Lewandowska and Sirko, 2008;Kopriva et al, 2009;Lee et al, 2012;Ciaffi et al, 2013), with some of these that include determinations of transcript levels and metabolite profiles (Hirai et al, 2003;Maruyama Nakashita et al, 2003;Nikiforova et al, 2005aNikiforova et al, , 2005bLunde et al, 2008;Kopriva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is shown that the S supply in form of sulphate can increase synthesis (Kuwajima and Kawai, 1997) and release of PS in Fe-deficient barley roots to improve the capacity of these plants to cope with Fedeficiency (Römheld and Marschner, 1990). The impact of Fe deprivation on the S assimilation pathway has been recently investigated in durum wheat (Ciaffi et al, 2013). These metallophores although can bind with metals other than Fe and Zn, highest affinity is reported for Fe (III) leading to predominance of Fe-PS complex which is taken up by the roots through YS1/YSL family transporters (Curie et al, 2001).…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…A positive effect of sulphur fertilization on growth attributes (Ciaffi et al, 2013), grain yield (Zhao et al, 1999) and grain quality (Pompa et al, 2009) have been evidenced in different crops (Jarvan et al, 2008). Our result confirmed this as the measure of yield and its attributes indicated a positive impact of sulphur application at S30 over S0 condition.…”
Section: Relative Expression Of Sulphate (Sultr1; 1) and Iron (Ys1) Tmentioning
confidence: 99%
See 1 more Smart Citation